2010
DOI: 10.4081/ija.2010.333
|View full text |Cite
|
Sign up to set email alerts
|

Lupin Seed for the Crop-Livestock Food Chain

Abstract: The ban on animal protein supplements in animal nutrition and, particularly, the increase in the demand for alternative protein sources to replace soybean meal in organic farming has stimulated research on GM-free feeds and renewed interest in grain legumes. Of these lupin appears to be one of the more interesting and promising crops for ruminant diets, due to its key role in low-input cropping systems and its high protein content. The aim of this study was to evaluate the productive and nutritional characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
4
18
0
1
Order By: Relevance
“…Considering that plant breeders have developed so‐called ‘sweet lupines’ with low alkaloid content (<50 mg per 100 g) for human and animal diets, LT and LB can be considered ‘sweet lupines’ in comparison with the bitter MU, the historical variety less selected by geneticists. Lupanine was the most represented and sparteine the least represented alkaloid; these data are slightly higher than those observed by Reinhard et al in the alkaloid profile of L. albus , by Boschin et al in nine alkaloid‐poor varieties of L. albus and Lupinus angustifolius grown in two climatically contrasting Italian sites and by Gresta et al in nine sweet varieties of L. albus , Lupinus luteus and L. angustifolius cultivated in the Mediterranean region. Angustifoline has been observed at low levels in L. albus as reported by Wink et al ; nevertheless, a high quantity was found in MU.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Considering that plant breeders have developed so‐called ‘sweet lupines’ with low alkaloid content (<50 mg per 100 g) for human and animal diets, LT and LB can be considered ‘sweet lupines’ in comparison with the bitter MU, the historical variety less selected by geneticists. Lupanine was the most represented and sparteine the least represented alkaloid; these data are slightly higher than those observed by Reinhard et al in the alkaloid profile of L. albus , by Boschin et al in nine alkaloid‐poor varieties of L. albus and Lupinus angustifolius grown in two climatically contrasting Italian sites and by Gresta et al in nine sweet varieties of L. albus , Lupinus luteus and L. angustifolius cultivated in the Mediterranean region. Angustifoline has been observed at low levels in L. albus as reported by Wink et al ; nevertheless, a high quantity was found in MU.…”
Section: Resultsmentioning
confidence: 65%
“…As expected, very low concentrations of quinolizidine alkaloids were also observed in LB and LT, except for LB2, where the alkaloid level was higher than the limit of toxicity (67.9 mg per 100 g). MU showed higher levels of alkaloids (136–165 mg per 100 g) than LT (9.15–14.5 mg per 100 g) and LB (3.63–67.9 mg per 100 g); the data are in accordance with those reported by Gresta et al for L. albus cv. Multitalia (166 mg per 100 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently some obstacles are limiting the use of soya bean: the ban in organic livestock (EC Council Regulation 834/2007) due to the chemical treatment and its costs and availability strongly related with the price development of agricultural commodities on the world market. In Italy, there is an increasing interest in the use of Mediterranean legume grains, which are also important because they increase the sustainability of livestock systems (Calabrò et al., , ; Gresta et al., ), contributing to the improvement of soil structure, fixing atmospheric nitrogen to the soil and reducing the fertilization costs. Among these, lupin may represent a very interesting alternative to soya bean.…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated, however, the ability of pea to maximise the production per unit area of grain yield and feed energy (as Milk Feed Units) across the two regions (Table 3). Work by Gresta et al (2010) confirmed for southern Italy the greater grain and protein yield per unit area of white lupin relative to narrowleafed lupin or yellow lupin (Lupinus luteus L.). Incidentally, lupins offer the additional advantage of being immune to a key pest in Mediterranean regions such as broomrape (Orobanche spp.…”
Section: Feed Legume Cultivation Yield and Profitabilitymentioning
confidence: 95%